Pharmaceutical enterprises drug quality strategy Moran analysis considering government supervision and new media participation - Xu, Yanping; Zhu, Lilong (Frontiers in Public Health, 2023)
The improvement of drug quality requires not only the supervision of government, but also the participation of new media. Therefore, this paper constructs a Moran process evolutionary game model and analyses the evolutionary trajectory of N pharmaceutical enterprises’ drug quality strategic choice, and considers the choice of drug quality improvement strategy and drug cost reduction strategy. We obtain the conditions for the two strategies to achieve evolutionary stability under the dominance of external factors and the dominance of expected returns. The evolutionary process is simulated by MATLAB 2021b. The results show that, first of all, when the government penalty is high, the drug quality improvement strategy tends to become an evolutionary stable solution. What’s more, when the government penalty is low and the new media influence is low, the drug cost reduction strategy is easier to take root. The higher the new media influence, the higher the probability that pharmaceutical enterprises choose the drug quality improvement strategy. Thirdly, when the number of pharmaceutical enterprises is lower than a threshold, the drug quality improvement strategy is easier to take root. Finally, the drug quality improvement strategy is dominant when the quality cost factor is low and the government penalty is high, the drug cost reduction strategy is dominant when the quality cost factor is high and the government penalty is low. Above all, this paper provides countermeasures and suggestions for the drug quality improvement of pharmaceutical enterprises in practice.